Kebahagiaan Era Kontemporer Perspektif Eksistensialisme Jean Paul Sartre dan Logoterapi Viktor E. Frankl: Contemporary Happiness Perspective of Jean Paul Sartre's Existentialism and Viktor E. Frankl's Logotherapy - Anahdiah, Shofia; Mustofa, M. Lutfi; Habib, Zainal (Jurnal Filsafat Indonesia, 2025)
The world is moving faster and humans are required to adapt to the times, so that feelings of stress and unhappiness arise that can make individuals feel uncomfortable, such as frustration, anxiety, feeling useless, and causing mental disorders. Various thoughts and theories about the human journey in search of the meaning of life and happiness have emerged from various disciplines, such as philosophy and psychology. This study aims to conduct a comprehensive analysis of the perspective of happiness according to Sartre's existentialism and Frankl's logotherapy, and to explore its implications in the context of contemporary human life. Jean-Paul Sartre, a leading existentialist philosopher and Viktor Frankl, a psychiatrist who developed logotherapy highlight the essential aspects of human life that are relevant to the search for meaning and happiness through monumental written works. This study uses a comparative analysis method, by collecting and analyzing data from relevant primary and secondary sources. The comparison between Sartre and Frankl's perspectives on happiness includes identifying similarities and differences in the approaches, concepts, and implications of the two theories. Based on the results of the analysis of Sartre and Frankl's approaches to achieving happiness, it can be seen that Sartre's approach can help humans feel free to determine the meaning of life, without guidance from external values, while Frankl's approach can help individuals who are experiencing suffering to be able to take the positive side of the events, they experience so that they find the meaning of their lives. Sartre and Frankl's thoughts offer valuable insights for individuals seeking happiness and emotional well-being in the modern era, although there are criticisms of these views. Sartrean freedom teaches to live with authenticity and integrity, while Frankl's approach provides tools to overcome suffering and find deeper meaning in life. Both approaches provide a strong framework for achieving sustainable emotional well-being. The conclusion that can be drawn from the study is that Sartre and Frankl's approaches are relevant to helping individuals in the contemporary era find happiness in various conditions, but this study still needs to be developed to be able to explore and understand the concept of finding happiness in the contemporary era so that it can be effectively applied as time goes by.